Survey of Student Interest in Participating in Physical Education Learning at MAN 1 Malang - Amiq, Fahrial; Mutohir, Toho Cholik; Suroto, Suroto; Saputro, Yulianto Dwi (Physical Education, Health and Recreation Study Program, Universitas Insan Budi Utomo, Indonesia, 2022)
The purpose of this study was to determine the interest of students in participating in the learning of Physical Education, Sports, and Health at MAN 1 Malang. The method used is a survey, the data collection technique uses a questionnaire, and the scores obtained from the questionnaire are then analyzed using descriptive and quantitative analysis as outlined in the form of percentages. The sample used in this study were students of MAN 1 Malang class X-XII, with a total of 90 students. Sample selection was made by using a simple random sampling technique. The data analysis technique used in this study is the analysis of prerequisite tests, namely validity tests (instruments) and reliability tests. Based on the results of data analysis, it can be found that the results of students' interest in participating in Physical Education, Sports, and Health learning at MAN 1 Malang are in the high category with the highest frequency consideration, as many as 36 students or 40%. The results of infrastructure facilities on student interest in participating in Physical Education, Sports, and Health learning at MAN 1 Malang are in the high category, namely as many as 36 students or 40%. Based on the results of the study, it can be concluded that the student's interest in participating in the learning of Physical Education, Sports, and Health at MAN 1 Malang is in the high category. Meanwhile, judging from the factors of facilities and infrastructure on students' interest in participating in the learning of Physical Education, Sports, and Health at MAN 1 Malang is in the high category.